Intimate Friendship as a Pillar of Self-Esteem Formation in Adolescents from Broken Homes - Anisyah Anisyah; Khoiriyah Ulfah; Erwanto Erwanto (Psikostudia : Jurnal Psikologi, 2025)
This study aims to explore the role of intimate friendship in supporting emotional well-being and self-esteem of late adolescents from broken homes. Adolescents from broken homes tend to experience emotional stress and obstacles in expressing themselves, caused by minimal support and communication from their parents. This situation encourages them to seek other sources of support outside the family, especially through the presence of close friends who can provide space to tell stories and become a source of emotional reinforcement. This study uses a qualitative approach using the phenomenological method, this study involved in-depth interviews with three adolescents from disharmonious family backgrounds. The results show that intimate friendship plays an important role in building self-esteem, reducing loneliness, improving emotional management, and strengthening self-acceptance. Emotional support from close friends also helps deal with psychological stress due to family conflict. Key factors such as trust, loyalty, and social support are key to the success of this relationship. These findings emphasize the importance of strong social relationships as a strategy to deal with emotional challenges and provide direction for psychological interventions that focus on strengthening interpersonal relationships. Penelitian ini bertujuan mengeksplorasi peran intimate friendship dalam mendukung kesejahteraan emosional dan self-esteem remaja akhir dari keluarga broken home. Remaja yang berasal dari keluarga broken home cenderung mengalami tekanan emosional dan hambatan dalam mengekspresikan diri, yang disebabkan oleh minimnya dukungan dan komunikasi dari orang tua. Situasi ini mendorong mereka untuk mencari sumber dukungan lain di luar keluarga, khususnya melalui kehadiran sahabat dekat yang mampu memberikan ruang untuk bercerita dan menjadi sumber penguatan secara emosional. Penelitian ini menggunakan pendekatan kualitatif metode fenomenologi, studi ini melibatkan wawancara mendalam dengan tiga remaja berlatar belakang keluarga tidak harmonis. Hasilnya menunjukkan bahwa intimate friendship berperan penting dalam membangun harga diri, mengurangi kesepian, meningkatkan pengelolaan emosi, dan memperkuat penerimaan diri. Dukungan emosional dari teman dekat juga membantu menghadapi tekanan psikologis akibat konflik keluarga. Faktor utama seperti kepercayaan, kesetiaan, dan dukungan sosial menjadi kunci keberhasilan hubungan ini. Temuan ini menekankan pentingnya hubungan sosial yang kuat sebagai strategi menghadapi tantangan emosional, serta memberi arah bagi intervensi psikologis yang fokus pada penguatan relasi interpersonal.